Cutaneous Necrosis As a Result of Isosulphane Blue Injection in Mammarian Sentinel Lymph Node Mapping: Report of Two Cases - Bircan, Huseyin Y (Libertas Academica, 2014)
Skin-sparing mastectomy with sentinel lymph node biopsy (SLNB) and synchronous breast reconstruction are widely used in breast cancer surgery nowadays. Difficulties in feeling confident in this technique and postoperative surgical complications are the major obstacles against the widespread usage of this technique. Compared with the other surgical techniques, the complications are hard to treat. Cutaneous necrosis because of methylene blue used for sentinel lymph node mapping in patients who underwent skin-sparing mastectomy and SLNB is already reported in the literature. We present here two cases with cutaneous necrosis because of isosulphane blue injection after skin-sparing mastectomy and SLNB as a rare complication of dye injection.